Challenge N- versus O-six-membered annulation: FeCl3-catalyzed synthesis of heterocyclic N,O-aminals - Mari, Giacomo; De Crescentini, Lucia; Favi, Gianfranco; Mantellini, Fabio; Olivieri, Diego; Santeusanio, Stefania (Beilstein Journal of Organic Chemistry, 2024)
A new class of heterocyclic N,O-aminal and hemiaminal scaffolds was successfully obtained by means of a three-component reaction (3-CR) of 1,2-diaza-1,3-dienes (DDs), α-aminoacetals and iso(thio)cyanates. These stable imine surrogates are generated from key-substituted (thio)hydantoin intermediates through selective FeCl3-catalyzed intramolecular N-annulation.
Keywords: α-aminoacetals; fused-ring systems; heterocyclic hemiaminals; heterocyclic N,O-aminals; multicomponent reactions